ANALISIS ALIRAN INFORMASI KOMUNIKASI PADA LAYANAN ANTAR (DELIVERY SERVICE) KUTIPAN AKTA KELAHIRAN DI KECAMATAN PADANG TIMUR KOTA PADANG - Benny Prima; Erwin Erwin; Jendrius Jendrius (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This article discusses the flow of information on communication in the management of Public Services Plus Inter-Quotation Service Birth Certificate and the distortion of the flow of information in the management of Public Services Plus Inter-Citation Services for Birth Certificates in Padang Timur District, Padang City. Information flow of communication in the management of Public Services Plus Inter-Citation Services for Birth Certificates in Padang Timur Subdistrict, Padang City, seen from the leadership communication skills in this case the Head of East Padang Subdistrict. Formal communication has taken place in accordance with hierarchical levels of authority that are valid and related to the task. Formal communication is centered on leadership decisions and serves to give orders, coordination, and control over subordinate activities. Effective formal communication requires preparation and planning regarding goals, target recipients, determining situations, times and places. Formal communication conducted in the sub-district of Padang Timur uses oral and written channels. While the distortion of information flow in the management of Public Service Plus Delivery Service for Birth Certificate in Padang Timur Subdistrict, Padang City includes Employee Experience and Education Levels, Psychological Disorders, Cultural or Habit Obstacles, Facilities and Infrastructure and not yet available Padang Timur District Officers and Disdukcapil task of writing the name and address of the destination.